2018
DOI: 10.1155/2018/4141756
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplants from Older Deceased Donors: Use of Preimplantation Biopsy and Differential Allocation to Dual or Single Kidney Transplant according to Histological Score Has No Advantages over Allocation to Single Kidney Transplant by Simple Clinical Indication

Abstract: Background Grafts from elderly donors (ECD) are increasingly allocated to single (SKT) or dual (DKT) kidney transplantation according to biopsy score. Indications and benefits of either procedure lack universal agreement. Methods A total of 302 ECD-transplants in period from Jan 1, 2000, to Dec 31, 2015, were allocated to SKT (SKTpre) on clinical grounds alone (before Dec 2010, pre-DKT era, n = 170) or according to a clinical-histological protocol (after Dec 2010, DKT era, n = 132) to DKT (n = 48), SKT biopsy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The lack of benefit experienced by these centres could be attributed to different histological scoring systems used, 23 interpathologist variability in reporting, 24,25 and selection of patients who are already prognostically adverse. 26 Locally, the average waiting time for kidney transplantation is 9 years, and the use of kidneys with very poor histological scores had been considered. On the other hand, the median age at which waitlisted patients receive a kidney is 48 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of benefit experienced by these centres could be attributed to different histological scoring systems used, 23 interpathologist variability in reporting, 24,25 and selection of patients who are already prognostically adverse. 26 Locally, the average waiting time for kidney transplantation is 9 years, and the use of kidneys with very poor histological scores had been considered. On the other hand, the median age at which waitlisted patients receive a kidney is 48 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had not demonstrated the value of pre‐transplant biopsy assessment. The lack of benefit experienced by these centres could be attributed to different histological scoring systems used, 23 inter‐pathologist variability in reporting, 24,25 and selection of patients who are already prognostically adverse 26 …”
Section: Discussionmentioning
confidence: 99%
“…Two recent Italian studies on the utility of pre-implantation biopsy in allocating ECD kidneys[4,55] concluded that histological evaluation was not superior to donor clinical evaluation in allocating ECD kidneys either as a single kidney or as a dual kidney transplant. The authors concluded that, according to their experience, the histological score poorly evaluates the donor kidney quality.…”
Section: Histological Evaluation Of Donor Kidneysmentioning
confidence: 99%
“…Historically, the evaluation of the kidneys from ECDs has been made histologically by the so-called zero-time biopsy[4], by clinical evaluation of the donor by different kidney allocation scores or by a combination of histological and clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Deciding which kidneys from older donors should be implanted as two single transplants, as a dual transplant, or which should be discarded is challenging. Although some centers in the United Kingdom and internationally use preimplantation histologic evaluation to help identify which kidneys should be implanted as duals (2,8,9), no clinical or histologic parameters have been widely accepted to aid utilization decisions (10)(11)(12)(13)(14)(15)(16). There is also little clinical guidance regarding recipient selection, and many offering policies for kidneys from older donors are based on donor criteria alone (17,18).…”
Section: Introductionmentioning
confidence: 99%